A red baby should not be taken too lightly. - Faletra, Flavio; Bruno, Irene; Berti, Irene; Pastore, Serena; Pirrone, Angela; Tommasini, Alberto (Acta Paediatr, 2012)
AIM: To identify clinical and laboratory features that can drive the differential diagnosis of a primary immunodeficiency diseases in patients with ectodermal defects. METHODS: Analysis of selected teaching cases. RESULTS: We identified four exemplary cases that allowed to point out specific clues. CONCLUSIONS: A careful evaluation of immune and ectodermal signs is the key to the diagnosis. Therefore, a multidisciplinary approach can lead to diagnosis and to an appropriate treatment in most of the cases.
Keywords: Child, Preschool; Dermatitis; Ectodermal Dysplasia; Female; Humans; Immunologic Deficiency Syndromes; Infant; Male; Netherton Syndrome; Severe Combined Immunodeficiency; Skin